Epithelial Aryl Hydrocarbon Receptor Protects From Mucus Production by Inhibiting ROS-Triggered NLRP3 Inflammasome in Asthma - Xinyue Hu (Frontiers Media S.A., 2021)
BackgroundDespite long-standing recognition in the significance of mucus overproduction in asthma, its etiology remains poorly understood. Muc5ac is a secretory mucin that has been associated with reduced pulmonary function and asthma exacerbations.ObjectivesWe sought to investigate the immunological pathway that controls Muc5ac expression and allergic airway inflammation in asthma.MethodsCockroach allergen-induced Muc5ac expression and aryl hydrocarbon receptor (AhR) signaling activation was examined in the human bronchial epithelial cells (HBECs) and mouse model of asthma. AhR regulation of Muc5ac expression, mitochondrial ROS (Mito-ROS) generation, and NLRP3 inflammasome was determined by AhR knockdown, the antagonist CH223191, and AhR-/- mice. The role of NLRP3 inflammasome in Muc5ac expression and airway inflammation was also investigated.ResultsCockroach allergen induced Muc5ac overexpression in HBECs and airways of asthma mouse model. Increased expression of AhR and its downstream genes CYP1A1 and CYP1B1 was also observed. Mice with AhR deletion showed increased allergic airway inflammation and MUC5AC expression. Moreover, cockroach allergen induced epithelial NLRP3 inflammasome activation (e.g., NLRP3, Caspase-1, and IL-1β), which was enhanced by AhR knockdown or the antagonist CH223191. Furthermore, AhR deletion in HBECs led to enhanced ROS generation, particularly Mito-ROS, and inhibition of ROS or Mito-ROS subsequently suppressed the inflammasome activation. Importantly, inhibition of the inflammasome with MCC950, a NLRP3-specifc inhibitor, attenuated allergic airway inflammation and Muc5ac expression. IL-1β generated by the activated inflammasomes mediated cockroach allergen-induced Muc5ac expression in HBECs.ConclusionsThese results reveal a previously unidentified functional axis of AhR-ROS-NLRP3 inflammasome in regulating Muc5ac expression and airway inflammation.